Association membership and generalised trust: Are connections between associations losing their value? - Benny Geys (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Research linking civic engagement to citizens' democratic values, generalized trust, cooperative norms, and so on often implicitly assumes such connections are stable over time. This article argues that, due to changes in the broader institutional environment, the engagement-values relation is likely to generally lack temporal stability. We investigate this empirically by analysing the engagement-trust relation using World Values Survey (WVS) data from the 1990 and 2000 waves. Overall, our results show that voluntary association memberships remain positively associated with generalised trust in both samples, but evidence that memberships in connected associations are better than in isolated ones appears, at best, scant in more recent years.
Keywords: 330; voluntary associations; generalised trust; world values studies; social networks; longitudinal analysis; Ehrenamtliche Arbeit; Mitgliedschaft; Vertrauen; Soziale Werte; Soziales Netzwerk; Welt